PENGEMBANGAN MODEL PEMBELAJARAN TEMATIK SENI DAN BUDAYA MENGGUNAKAN VIDEO TEATERIKALISASI COWONGAN DI SEKOLAH DASAR - Anastasia Dwi Wiwik Irawati; Kuntoro Kuntoro; Akhmad Jazuli (Universitas Muhammadiyah Purwokerto, 2019)
This study aims to develop a thematic learning model of art and culture usingvideo theatericalization of “Cowongan” for students in elementary schools. Thisresearch is a research development that aims to improve the ability to verbalize“Kidung Kasengsaraan Mangsa Ketiga” with the Banyumas dialect. The researchdesign uses R and D Data collection techniques in research gather information, productdesign, product validation, product testing, design revision, trial use, product revision,mass production, and dissemination. These data sources are interviews, observations,taking questionnaires, and tests. The sampling technique uses cluster sampling as thepopulation of SDN 4 Sokanegara students. The results of research in verbalizing thegeguritan include laval, intonation, placement of pauses, and expressions. Theobservations of researchers obtained data that the average posttest results that theexperimental class reached 90% of the expected score, while the average control classreached 75.75% of the expected score. The results of the effectiveness test in theresearch prove that the class that uses the product is better than the one that does notuse the product so that the ability to speak up using the Banyumas dialect is moreeffective.